Healthy subjects gut microbiome modulation by Bacillus coagulans BCP92 - Sohel S. Shaikh; Farhana Malek (Medicine, 2026)
Background: Probiotics are recognized for their ability to restore balance in the gut microbiome during dysbiosis. However, their effects on the gut microbiota of healthy individuals have rarely been investigated. This study aimed to evaluate the safety and efficacy of Bacillus coagulans (Heyndrickxia coagulans ) BCP92 and its influence on microbiota composition in healthy subjects. Methods: In the present investigation, healthy participants (n = 48) were allocated into 2 groups and administered either Bacillus coagulans BCP92 capsules (1 billion CFU/capsule) or a placebo containing maltodextrin for 42 days. Microbiome composition and short-chain fatty acid analyses were subsequently conducted. Results: Analysis of metagenomes showed no major alterations in gut microbiome composition among participants who received B. coagulans BCP92 supplementation. However, subtle beneficial changes were observed in the treatment group, suggesting that probiotic administration may increase advantageous phyla, classes, orders, families, and some genera, while decreasing potentially harmful groups. A slight increase in short-chain fatty acids (SCFA) was also observed in the fecal samples. Conclusions: This study implies that extended supplementation with the probiotic B. coagulans BCP92 may lead to substantial improvements in gut microbiome composition and SCFA levels.